Communication between the distal interphalangeal joint and the navicular bursa in the horse at Computed Tomography Arthrography. (4th January 2019) - Hontoir, Fanny; Rejas, Erika; Falticeanu, Ana; Nisolle, Jean‐François; Simon, Vincent; Nicaise, Charles; Clegg, Peter D.; Vandeweerd, Jean‐Michel E.
Abstract: Diffusion of drugs injected into the distal interphalangeal joint or the navicular (podotrochlear) bursa can influence diagnosis and treatment of foot pain. Previous anatomical and radiographic studies of the communication between these synovial structures have produced conflicting results and did not identify the location of any communication if present. This anatomic study aimed to assess the presence and site of communication between the distal interphalangeal joint and the navicular bursa in the horse by computed tomography arthrography. Sixty‐six pairs of cadaver forelimbs were injected with contrast medium into the distal interphalangeal joint and imaged by computed tomography arthrography. The presence of a communication, location of the communication and additional structural changes were assessed. Navicular bursa opacification occurred in 7 distal limbs (5.3%) following distal interphalangeal joint injection. One limb showed a communication through the T‐ligament and 6 limbs showed a communication through the distal sesamoidean impar ligament. In 3 cases, the communication through the distal sesamoidean impar ligament was associated with a distal border fragment. Our study showed that communication between the distal interphalangeal joint and navicular bursa is uncommon and inconsistent. Clinically, the presence of a communication could (1) influence the interpretation of diagnostic analgesia of the distal interphalangeal joint or the navicular bursa by facilitating the diffusion of local anaesthetic between these structures; (2) allow the drug and its potential adverse effects to spread from the treated synovial cavity to the non‐targeted synovial cavity; (3) be responsible for the failure of joint drainage in the case of sepsis.